The vanishing at Loxby Manor [large type] - Wilson, Abigail (Thorndike Press large print Christian romance series., 2022)
"Disappearances, strange activities in the night, and secret organizations abound in this mysterious Regency romance. Haunted by the assault she's kept hidden over the past four years, Charity Halliwell finally has a chance to return home to the quaint village she left more than five years before and the happy life she wants so badly to reclaim. All she needs is good conversation with her old friend and an opportunity to find a governess position, and she can leave the fear and guilt behind. But the family who agrees to her yearlong visit turns out to be a far cry from the one she thought she knew, particularly when her friend disappears and the one man she made certain would not be at the house is forced to return. How can she possibly heal and claim her independence when day in, day out she must face the only gentleman who ever held a piece of her heart Piers Cavanagh was branded a coward when he failed to show up for a duel he arranged. He had his reasons, of course, but disclosing them would hurt far more than continuing life as an outcast. And worse, with the mysterious departure of his sister, the strange nightly occurrences in the ruins of an old abbey, and the uncomfortable whispers of a secret organization, Piers must overcome his aversion to society and work with the last person he ever thought he would get the chance to speak to again--the girl whose heart he had no choice but to break"--